Effectiveness of intrauterine condom tamponade in atonic postpartum hemorrhage - Pradhan, Binita; Shrestha, Reena; Todi, Sushila (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Postpartum hemorrhage(PPH) is the leading cause of maternal mortality. The intrauterine balloon tamponade is the efficient and economical means to treat atonic PPH so this study was done to evaluate the outcome of uterine balloon tamponade in atonic PPH.Method: This was a retrospective study conducted at the Patan Academy of Health Sciences Lalitpur, Kathmandu from January 2017 to December 2019. It included women with postpartum haemorrhage due to uterine atony in whom medical treatment had failed.Result: The condom tamponade was successful in 94.7% women with uterine atony, who did not respond to uterotonic drugs and 5.3% required peripartum hysterectomy. Majority of women were in the 25-29 years age group. 73.3% were multigravida and 63.2% had vaginal delivery. No case of febrile morbidity and wound sepsis was noted.Conclusion: The study concludes the use of condom tamponade as an effective means of controlling atonic PPH. It is safe, easily available, inexpensive, minimally invasive, does not require anesthesia, easy to use and can be performed by any level of health personnel with some training.